Challenges of Increasing Childcare Center Compliance With Nutrition Guidelines: A Randomized Controlled Trial of an Intervention Providing Training, Written Menu Feedback, and Printed Resources. Issue 3 (March 2019) - Finch, Meghan; Seward, Kirsty; Wedesweiler, Taya; Stacey, Fiona; Grady, Alice; Jones, Jannah; Wolfenden, Luke; Yoong, Sze Lin
Purpose: To assess the effectiveness of an intervention including training, provision of written menu feedback, and printed resources on increasing childcare compliance with nutrition guidelines. Design: Parallel group randomized controlled trial. Setting: Hunter New England region, New South Wales, Australia. Participants: Forty-four childcare centers that prepare and provide food on-site to children while in care. Intervention: The intervention was designed using the Theoretical Domains Framework, targeted managers, and cooks and included implementation strategies that addressed identified barriers. Measures: Outcomes included the proportion of menus providing food servings (per child) compliant with overall nutrition guideline recommendations and each individual food group assessed via menu assessments. Cook knowledge of recommendations, intervention acceptability, adverse events, and barriers were also assessed via questionnaires with cooks and managers. Analysis: Logistic regression models, adjusted for baseline values of the outcome. Results: At baseline and follow-up, zero centers in the intervention and control groups were compliant with the overall menu guidelines or for the vegetable and meat food groups. Follow-up between-group differences in compliance for discretionary (33.3 vs 5, P = .18), dairy (41.7 vs 15, P = .16), breads and cereals (8.3 vs 10 P = 1.00), and fruit (16.7 vs 10, P = .48) were all nonsignificant. Relative to the control group, intervention centers showed a significantly greater increase in percentage of cooks with correct knowledge for vegetable servings (93.3 vs 36.4, P = .008). Conclusion: Although the application of the theoretical framework produced a broader understanding of the determinants of menu compliance, due to the complexity of guidelines, limited follow-up support, lower training uptake, and low intervention dose, the intervention was not effective in supporting the practice change required.